Ecological status of a Margaritifera margaritifera (Linnaeus, 1758) population at the southern edge of its distribution (River Paiva, Portugal) - Sousa, Ronaldo Gomes (2013)
An important population of the critically endangered pearl mussel Margaritifera margaritifera (Linnaeus, 1758) was surveyed at the edge of its southern distribution (River Paiva, Portugal). Although an earlier study suggested that this population had a very low number of individuals (<500), a narrow distribution, and was mainly comprised by old specimens our data contradict these findings. Our assessment estimated a population with probably more than 5,000 individuals distributed across 80 km of the river length. From the 32 sites surveyed, 19 contained M. margaritifera with higher abundances verified in the middle and upper parts of the river (a maximum of 78 ind. per 100 m of river stretch was recorded). The pearl mussels showed a clear preference for areas near the banks, in shallow water, sandier and gravel sediments, and a high degree of riparian vegetation cover. The population structure was skewed with a very high percentage of large (and old) animals but 3.7 % of the individuals collected were juveniles (<60 mm in length); therefore, this population can be considered functional. Environmental characterization indicated that this river is still in excellent or good condition although some areas showed deterioration due to discharge of domestic effluents. The main conservation requirements of M. margaritifera in the River Paiva include maintaining the water quality (and if possible stopping the discharge of domestic effluents), increasing riparian vegetation cover, removing several weirs to increase connectivity, and increasing trout density.